Modernizing Dark Pool Infrastructure: Machine Consolidation via AKS - Rajat Shrivastava (International Journal of Intelligent Systems and Applications in Engineering, 2021)
A cloud-native modernization of dark pool trading infrastructure based on Azure Kubernetes Service is presented with the emphasis on machine consolidation, scalability, and low-latency performance. The common problems associated with traditional dark pool systems include: expensive infrastructure, lack of scalability and poor utilization of resources. The suggested architecture will use microservices, containerization, and Kubernetes-based orchestration to facilitate dynamic scaling and efficient workload management. It contains the basic elements such as Order Management Service, dark pool matching engine, trade execution service, and the real-time event streaming platform to provide smooth and fast trading operations. Simulated high-frequency trading load experimental evaluation has shown that there are significant performance gains, such as a maximum of 70% decrease in latency, a four-fold throughput increase, and improved resource usage. Moreover, the AKS-based system is attaining a high level of machine consolidation and cost optimization, which decreases the overhead of operations. The results demonstrate the usefulness of cloud-native solutions in improving the efficiency, scalability, and reliability of contemporary dark pool trading systems.